Internalisasi Karakter Islami Berbasis Projek Penguatan Profil Pelajar Pancasila (P5) di SMP Plus Al-Kautsar Malang - Nastiti, Sekar Arum; Rossidy, Imron (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The current moral degradation in the country illustrates the significance of character educatian. The purposed of this study was to examine how students at SMP Plus Al-Kautsar Malang internalize the values of the Pancasila students profile in order to develop Islamic character. The research focuses on the outcomes of the internalization of Pancasila student profile values in the development of Islamic character, along with a number of elements that facilitate and hinder this process. Descriptive qualitative methodology was employed in this study, along with methods for gatering data that included documentasion, interview, and observation. The findings of the study demonstraded that there were three primary phases in the process by which students at SMP Plus Al-Kautsar Malang internalized the significance of the Pancasila student profile in shaping their Islamic character. The first stage is value transformation, which involves distributing good moral values by providing direction and advice regarding good and bad values. The second stage is value transaction, which involves reciprocal communication between educators and students to ensure understanding of values. The third stage is the transinternalization of values, which involves habituation, Islamic activities, and project-based learning (P5). The strategies implemented include habituation, example, monitoring, and giving rewards and punishments. The results of the study show the strong influence that students have at SMP Plus Al-Kautsar Malang when internalizing the importance of the Pancasila student profile in shaping Islamic character. The students have succeeded in forming answers, independent, religious, and socially conscious.